Ceria/polymer nanocontainers for high-performance encapsulation of fluorophores - Katta, Kartheek (Beilstein J Nanotechnol, 2019)
We report the synthesis of high-performance organic–inorganic hybrid fluorescent nanocapsules comprising a polymer shell armored with an inorganic layer and a liquid core containing a fluorophore. The polymeric capsules are synthesized by free radical miniemulsion polymerization and contain covalently bound carboxylate surface functionalities that allow for the binding of metal ions through electrostatic interaction. A cerium(IV) oxide nanoparticle layer, formed in situ at the surface of the hybrid nanocapsules, acts as oxygen scavenger and keeps external reactive molecular oxygen from entering into the capsules, eventually resulting in a reduction of the photooxidation of encapsulated fluorescent molecules. This approach shows an increase in the fluorescence of the model organic fluorophore terrylene diimide by avoiding the ground-state molecular oxygen to react with electronically excited states of the fluorescent hydrocarbon molecule.